The discovery of glass and the methods and techniques of its manufacture in the antiquity. - rezzig, faiza (Journal of Social Sciences and Humanities, 2021)
The Glass is considered to be known certainly, even though its existence not appears natural. However, the successful transformation of glass into sand, then its use by multiples and different ways requires a lot of creativity and techniques. Also the question of discovery of the glass material had caused divergence and multiple points of view, so some opinions attribute it to the Phoenician, while other attribute the discovery of glass to ancient near East. Through the following historical and archeological study, we will try to approach its different opinions in order to know the ways of the glass through the epochs and stages of its development, in addition to the methods used for the ornament of glass and nature of oxides used in its decoration.